Smoking Effect on Oxidative Stress and Antioxidant Capacity of Cervical Mucus in Women with Primary Idiopathic Sterility – Observational Case-Control Study - Gordana Planinić Radoš; Željko Duić; Boris Lovrić; Josip Juras (Acta Clinica Croatica, 2024)
The aim of the study was to determine the effects of smoking on cervical mucus in women with primary idiopathic sterility. A prospective, case-control, observational, quantitative, and analytical study was carried out over a five-year period through ambulatory care. The first part of the study involved 140 healthy women (85 smokers and 55 non-smokers). The second part included 90 women (58 healthy, 32 suffering from sterility), grouped according to their smoking status. Concentrations of total proteins in cervical mucus solutions and homogenates of cervical surface cells and their mitochondria, thiocyanate and ascorbic acid, rhodanese activity, concentrations of cytochrome P-450 (mitochondria), lipid peroxidation and the total antioxidant capacity in homogenates of cervical surface cells, concentrations of superoxide O2, reduced gluthatione (GSH), advanced oxidation protein products (AOPP), and ferric reducing ability of plasma (FRAP) were measured. The measurements showed higher concentrations of thiocyanate, cytochrome P-450 and lipid peroxidation values, and lower concentrations of ascorbic acid, cytochrome P-450 activity and FRAP in smokers. Higher concentrations of superoxide O2, GSH, AOPP, and lower FRAP were found among smokers and women suffering from sterility. In conclusion, changes in oxidative stress and antioxidant capacity caused by smoking indicate that the quality of cervical mucus among patients suffering from sterility is lower compared to healthy women.